Student's perception of peer feedback in learning Mathematics - Ananda Anisa Zhafira; Syahra Artika; Wahyunengsih (MAXIMA : Jurnal Pendidikan Matematika, 2025)
This study aims to determine students’ perceptions of peer feedback in mathematics learning. The method used is quantitative descriptive, with data collection through a Likert scale questionnaire. The research participants consisted of 20 students randomly selected at several universities in Banten. The results showed that most students had a positive perception of peer feedback. High percentages of agreement were seen in the aspects of usefulness 82%, effectiveness 82%, its impact on understanding 81,25%, and mastery of mathematics material 82,5%. Lecturer support was also considered necessary 77,5% in facilitating feedback. However, 60% of students admitted to experiencing challenges in giving and receiving feedback, mainly due to awkwardness or uncertainty. The findings confirm that peer feedback increases activeness, collaboration, and understanding of mathematical concepts. Therefore, it is necessary to implement peer feedback that is structured and actively supported by lecturers, accompanied by adequate training and effective use of technology so that this practice can run more optimally.